(untitled) (Nordic Journal of African Studies, 2002)
The central thesis of this paper is that the definition of social phenomena is culturally determined, and, therefore, the explanation of health and illness is a function of culture. As a result, this has significant implications for health-seeking behaviour. The study, carried out in a Yoruba community, obtained ethnographic data through in-depth interview and non-participatory observation methods. The Yoruba worldview influences perceptions of health and illness and the prevention and cure of ill-health. In fact, the ’ayanmo’ mythology plays a significant role in the explanation of health conditions. While good health signifies a positive destiny (ayanmo rere), ill health is considered to be a negative destiny (ayanmo buruku). Pathways to prevention and cure usually favour the patronage of the traditional healing process, while hospital care is sought only when all other attempts have failed. Hence, the mortality rate is generally still high.